Pulsed wave tissue Doppler imaging for the quantification of contractile reserve in stunned, hibernating, and scarred myocardium. (14th April 2004) - Bountioukos, M; Schinkel, A F L; Bax, J J; Rizzello, V; Valkema, R; Krenning, B J; Biagini, E; Vourvouri, E C; Roelandt, J R T C; Poldermans, D
Abstract : Objectives: To assess whether quantification of myocardial systolic velocities by pulsed wave tissue Doppler imaging can differentiate between stunned, hibernating, and scarred myocardium. Design: Observational study. Setting: Tertiary referral centre. Patients: 70 patients with reduced left ventricular function caused by chronic coronary artery disease. Methods: Pulsed wave tissue Doppler imaging was done close to the mitral annulus at rest and during low dose dobutamine; systolic ejection velocity (Vs) and the difference in Vs between low dose dobutamine and the resting value (ΔVs) were assessed using a six segment model. Assessment of perfusion (with Tc-99m-tetrofosmin SPECT) and glucose utilisation (by 18 F-fluorodeoxyglucose SPECT) was used to classify dysfunctional regions (by resting cross sectional echocardiography) as stunned, hibernating, or scarred. Results: 253 of 420 regions (60%) were dysfunctional. Of these, 132 (52%) were classified as stunned, 25 (10%) as hibernating, and 96 (38%) as scarred. At rest, Vs in stunned, hibernating, and scar tissue was, respectively, 6.3 (1.8), 6.6 (2.2), and 5.5 (1.5) cm/s (p = 0.001 by ANOVA). There was a gradual decline in Vs during low dose dobutamine infusion between stunned, hibernating, and scar tissue (8.3 (2.6) v 7.8 (1.5) v 6.8 (1.9) cm/s, p < 0.001 by ANOVA). ΔVs was higher in stunned (2.1 (1.9) cm/s) than in hibernating (1.2 (1.4) cm/s, p < 0.05) or scarred regions (1.3 (1.2) cm/s, p = 0.001). Conclusions: Quantitative tissue Doppler imaging showed a gradual reduction in regional velocities between stunned, hibernating, and scarred myocardium. Dobutamine induced contractile reserve was higher in stunned regions than in hibernating and scarred myocardium, reflecting different severities of myocardial damage.